2021
DOI: 10.3390/ijms22137011
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nrl1 Domains Responsible for Interactions with RNA-Processing Factors and Regulation of Nrl1 Function by Phosphorylation

Abstract: Pre-mRNA splicing is a key process in the regulation of gene expression. In the fission yeast Schizosaccharomyces pombe, Nrl1 regulates splicing and expression of several genes and non-coding RNAs, and also suppresses the accumulation of R-loops. Here, we report analysis of interactions between Nrl1 and selected RNA-processing proteins and regulation of Nrl1 function by phosphorylation. Bacterial two-hybrid system (BACTH) assays revealed that the N-terminal region of Nrl1 is important for the interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Recently, by searching for novel spliceosome-associated factors in the fission yeast S. pombe , we identified Nrl1 protein as a factor that is required not only for proper pre-mRNA splicing of a subset of genes and non-coding RNAs, but also for the maintenance of genome stability by both suppressing R-loops and promoting HR repair. Interestingly, among its top interactors, we have identified the G-patch domain-containing protein Gpl1 [ 41 , 43 ]. It has also been shown that the gpl1 Δ mutant has canonical splicing defects with broad increases in pre-mRNA species and decreases in mature mRNA species, which suggested that Gpl1 might be a novel factor implicated in the regulation of pre-mRNA splicing [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, by searching for novel spliceosome-associated factors in the fission yeast S. pombe , we identified Nrl1 protein as a factor that is required not only for proper pre-mRNA splicing of a subset of genes and non-coding RNAs, but also for the maintenance of genome stability by both suppressing R-loops and promoting HR repair. Interestingly, among its top interactors, we have identified the G-patch domain-containing protein Gpl1 [ 41 , 43 ]. It has also been shown that the gpl1 Δ mutant has canonical splicing defects with broad increases in pre-mRNA species and decreases in mature mRNA species, which suggested that Gpl1 might be a novel factor implicated in the regulation of pre-mRNA splicing [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yeast cell powders (40 g) were prepared from frozen cell pellets using SPEX SamplePrep 6770 Freezer/Mill (SPEX SamplePrep, Metuchen, NJ, USA) cooled by liquid nitrogen. Proteins were extracted using IPP150 buffer (50 mM Tris pH 8.0, 150 mM NaCl, 10% glycerol, 0.1% NP-40, 1 mM PMSF and complete protease and phosphatase inhibitors) in a ratio of 1 g of yeast cell powder to 3 mL of IPP150 buffer and affinity purified as described previously [ 43 , 64 ]. Briefly, 500 µL of IgG Sepharose™ 6 Fast Flow beads (GE Healthcare, Uppsala, Sweden) was equilibrated with IPP150 buffer, mixed with protein extract and incubated on rotatory wheel for 2 h at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein-protein interaction between bait and prey reconstitutes adenylate cyclase, drives synthesis of cyclic-AMP, and leads to a red colony coloring on MacConkey agar plates (Fig 1A). This B2H system has previously been employed to quantitatively interrogate protein-protein interaction of various bacterial, fungal, and mammalian proteins [38][39][40][41]. We first sought to replicate our previous finding that protein VII interacts with HMGB1 [12] S1).…”
Section: Protein VII Directly Interacts With Hmgb1 By Bacterial Two-h...mentioning
confidence: 99%
“…A main challenge in the study of signalling networks is to show the physiological context and significance of putative interactions. The BACTH system has been extensively used to demonstrate the specificity of protein interactions [67][68][69][70][71][72]. However, despite initial optimism [41,56,57], reports of using it to approach the regulation of protein complexes are difficult to find [73].…”
Section: Lessons From Two-hybrid Assaysmentioning
confidence: 99%